The diagnostic conundrum in non-alcoholic fatty liver disease - Valerio Rosato; Mario Masarone; Andrea Aglitti; Marcello Persico (Open Exploration Publishing Inc., 2020)
Non-alcoholic fatty liver disease (NAFLD) has become the most common liver alteration worldwide. It encompasses a spectrum of disorders that range from simple steatosis to a progressive form, defined non-alcoholic steatohepatitis (NASH), that can lead to advanced fibrosis and eventually cirrhosis and hepatocellular carcinoma. On liver histology, NASH is characterized by the concomitant presence of significant fat accumulation and inflammatory reaction with hepatocellular injury. Until now, liver biopsy is still required to differentiate simple steatosis from NASH and evaluate the degree of liver fibrosis. Unfortunately, this technique has well-known limitations, including invasiveness and expensiveness. Moreover, it may be biased by sampling error and intra- or inter-observed variability. Furthermore, due to the increasing prevalence of NAFLD worldwide, to program a systematic screening with liver biopsy is not imaginable. In recent years, different techniques were developed and validated with the aim of non-invasively identifying NASH and assess liver fibrosis degrees. The non-invasive tests range from simple blood-tests analyses to composite scores and complex imaging techniques. Nevertheless, even if they could represent cost-effective strategies for diagnosing NASH, advanced fibrosis and cirrhosis, their accuracy and consequent usefulness are to be discussed. With this aim, in this review the authors summarize the current state of non-invasive assessment of NAFLD. In particular, in addition to the well-established tests, the authors describe the future perspectives in this field, reporting the latest tests based on OMICS, gut-miocrobioma and micro-RNAs. Finally, the authors provide an accurate assessment of how these non-invasive tools perform in clinical practice depending on the clinical context, with the aim of giving the clinicians a useful tool to try to resolve the diagnostic conundrum of NAFLD.